The Effect of Think-Pair-Share Strategy on Reading Comprehension of Narrative Text at the Eighth Grade of SMP GKPS 3 Pematang Siantar - Sihite, Enji Debora Sarina; Napitupulu, Selviana; Purba, Rudiarman (International Journal Corner of Educational Research, 2024)
This research aims to discover the Effect of Think-Pair-Share Strategy on students’ reading comprehension of the eighth-grade students of SMP GKPS 3 Pematang Siantar on Narrative text. This research used quantitative research with quasi experimental method. The data were collected through tests. The sample of this research were the VIII-2 as Experimental group and VIII-1 as Control group. The test was carried out with pre-test and post-test to students using narrative text. As a result, the researchers found the mean score in experimental class from pre-test to post-test were 25.92 and 78.14. The mean score in control class from pre-test to post-test were 32.22 and 56.81. The t-test value was 9.5, at a level of significances 0f 5% (=0.05), whereas t-table was 2.007, or t-test>t-table. Therefore, the Alternative Hypothesis (Ha) was accepted and the Null Hypothesis (H0) was rejected. Hence, there is a significant effect of using Think-Pair-Share Strategy to the reading comprehension at the Eight grade students of SMP GKPS 3 Pematang Siantar.